ChemInform Abstract: (R/S)‐BINOL‐α‐Phosphoryloxy Enecarbamate‐Mediated and (R/S)‐Titanium(IV) BINOLates‐Catalyzed Enantioselective Intramolecular Heck/Aza‐Diels—Alder Cycloaddition (IHADA): An Expedient Methodology. Issue 14 (8th April 2014) - Khan, Imran A.; Saxena, Anil K.
Abstract The conversion of o‐vinyl substituted N‐Boc‐N‐acetyl anilines to enecarbamates and subsequent Diels—Alder reaction in the presence of enantiopure BINOL as chiral source is developed.